Does ChatGPT Add Value to University Students’ Academic Performance? - Kaur, Parveen; Jawaid, Arif; Qi, Rochelle Ooi Jin; Rokman, Raes Dashreen bin Che Mohd; Awai, Sadra Selmah Anak; Liew, Samantha Suntie; Yunus, Seri Nurellisa binti Mohd (International Journal of Membrane Science and Technology, 2023)
The researchers were concerned about the effectiveness of ChatGPT with respect to students’ educational performance. This was because a lot of students were producing the assignments with little substantial evidence drawn from their own effort. To examine the extent of their personal contribution in academic work, a randomly selected group of university students were administered a questionnaire. The questionnaire comprised demographic information of the students, ChatGPT validity, reliability, advantages, disadvantages, and recommendations. The data analysis was carried out using Microsoft Excel. It was found out that the ChatGPT is useful academic resource. However, it should be used appropriately without compromising academic standards and honesty. More research with large diverse student community may bring useful results.